Methodological Approaches To Assess Innate Immunity and Innate Memory in Marine Invertebrates and Humans - Auguste, Manon; Melillo, Daniela; Corteggio, Annunziata; Marino, Rita; Canesi, Laura; Pinsino, Annalisa; Italiani, Paola; Boraschi, Diana (Frontiers in Toxicology, 2022)
Assessing the impact of drugs and contaminants on immune responses requires methodological approaches able to represent real-life conditions and predict long-term effects. Innate immunity/inflammation is the evolutionarily most widespread and conserved defensive mechanism in living organisms, and therefore we will focus here on immunotoxicological methods that specifically target such processes. By exploiting the conserved mechanisms of innate immunity, we have examined the most representative immunotoxicity methodological approaches across living species, to identify common features and human proxy models/assays, with emphasis on the application of the ARRIVE guidelines on reporting animal research, in order to strengthen the quality and usability of immunotoxicology research data. Three marine invertebrate organisms are examined in comparison with humans, i.e., bivalve molluscs, tunicates and sea urchins. In vivo and in vitro approaches are compared, highlighting common mechanisms and species-specific endpoints, to be applied in predictive human and environmental immunotoxicity assessment, in compliance with the 3R principle of Replacement, Refinement and Reduction of Animals in Research.